Digital Transformation in Management Human Resources Strategic : Integration Approach Adaptive and Cognitive - Kasih Prihantoro; Mia Kusmiati (International Forum of Researchers and Lecturers, 2025)
Purpose – This article aim For develop approach new in management source Power strategic human resources with integrate dimensions adaptive and cognitive in context digital transformation of organizations . Research This based on synthesis theoretical from works Prihantoro et al . (2022–2023), in order to review return the role of HR as driver main superiority competitive based knowledge in the era of disruption technology . Design/ methodology / approach – This article use method studies library conceptual with approach qualitative- descriptive analysis done to six work main topic that discusses strategic HR topics , digitalization organization and learning organization . Synthesis done For building an integrative model that emphasizes influence digital transformation towards performance and development of organizational human resources . Findings – Results of analysis show that approach adaptive-cognitive can strengthening HR strategy in face change environment business . Merger digital competence , ability Study organization , as well as leadership transformative proven become key in optimize HR functions in general strategic . HR is not Again only nature administrative , but is driving force main innovation and efficiency . Implications practical – Organization need designing repeat digital learning- based HR policies , building ecosystem management knowledge , as well as push culture Innovation . Data- driven and intelligence-driven HR practices artificial is also recommended For taking decision strategic . Originality / Value – This article offer novelty conceptual through integration theory learning organization and approach mark in digital HR management . Contribution This expand traditional HRM coverage to realm more strategic​ responsive to challenge technology .